Genome-wide identification of the GhARF gene family reveals that GhARF2 and GhARF18 are involved in cotton fibre cell initiation. (12th June 2018) - Xiao, Guanghui; He, Peng; Zhao, Peng; Liu, Hao; Zhang, Li; Pang, Chaoyou; Yu, Jianing
Abstract : Auxin may activate several transcription factors via GhARF2 and GhARF18 proteins to regulate cotton seed fibre cell initiation. Abstract: Auxin signalling plays an essential role in regulating plant development. Auxin response factors (ARFs), which are critical components of auxin signalling, modulate the expression of early auxin-responsive genes by binding to auxin response factor elements (AuxREs). However, there has been no comprehensive characterization of this gene family in cotton. Here, we identified 56 GhARF genes in the assembled Gossypium hirsutum genome. This gene family was divided into 17 subfamilies, and 44 members of them were distributed across 21 chromosomes. GhARF6 and GhARF11 subfamily genes were predominantly expressed in vegetative tissues, whereas GhARF2 and GhARF18 subfamily genes were highly expressed during seed fibre cell initiation. GhARF2-1 and GhARF18-1 were exclusively expressed in trichomes, organs similar to cotton seed fibre cells, and overexpression of these genes in Arabidopsis enhances trichome initiation. Comparative transcriptome analysis combined with AuxRE prediction revealed 11 transcription factors as potential target genes of GhARF2 and GhARF18 . Six of these genes were significantly expressed during seed fibre cell initiation and were bound by GhARF2-1 and GhARF18-1 in yeast one-hybrid assays. Our results suggest that GhARF2 and GhARF18 genes may be key regulators of cotton seed fibre initiation by regulating the expression of several transcription factor genes. This study deepens our understanding of auxin-mediated initiation of cotton seed fibre cells and helps us in breeding better cotton varieties in the future.